If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -4x = -2x + -12 Reorder the terms: 18 + -4x = -12 + -2x Solving 18 + -4x = -12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 18 + -4x + 2x = -12 + -2x + 2x Combine like terms: -4x + 2x = -2x 18 + -2x = -12 + -2x + 2x Combine like terms: -2x + 2x = 0 18 + -2x = -12 + 0 18 + -2x = -12 Add '-18' to each side of the equation. 18 + -18 + -2x = -12 + -18 Combine like terms: 18 + -18 = 0 0 + -2x = -12 + -18 -2x = -12 + -18 Combine like terms: -12 + -18 = -30 -2x = -30 Divide each side by '-2'. x = 15 Simplifying x = 15
| -8g+6=(6g+8) | | 4-5x=x-14 | | -5x+17=-38 | | 90=30y+30 | | X*3-3=-6 | | 8n+5=77 | | 3x^2+2x+33=0 | | 14-x=12-x+2 | | 14-2x=22 | | -12=3-5k | | 7x+3y-4x+5y=8 | | 3a^2-4a+2=0 | | 2x+5+6x=8x-4 | | 1/3*(2b+9)=2/3(b+9/2) | | 5x=44 | | 3y-1+y+31=8y+30-6y | | 8X+32=2X+4 | | k(3)=9 | | -12t=-204 | | 3.4x-5.25=5.1-3.5x | | x+14=100 | | 8t-48+t^2= | | 5x+19y=-29 | | ay+1=by-1 | | 6.4x-3.7x=-48.6 | | 3(x+4)-12(x-8)=18 | | 12+194f=20f | | 2.25+5y=10y-.25 | | xq=1-xp | | 20c=30c-50 | | 2x^2=3x+7 | | 8*4*k+9*5=(36-4)k-(2*5) |